Antioxidant and Skin Whitening Activities of Sub- and Super-Critical Water Treated Rutin - Yeon Jae Jo; Dan Hee Yoo; In Chul Lee; Junsoo Lee; Heon Sang Jeong (Molecules, 2022)
We focused on the functional components, antioxidant activity, skin-whitening, and anti-wrinkle properties of subcritical and supercritical water (SCW)-treated rutin. Rutin treatments were performed at the following temperature and pressure conditions: 200 °C/15 bar, 300 °C/100 bar, and 400 °C/250 bar. ABTS and DPPH radical scavenging activities and reducing power presented their highest values (1193.72 mg AAE/g, 728.73 mg AAE/g, and 0.65, respectively) at 300 °C/100 bar. The tyrosinase inhibitory activity of SCW-treated rutin was 21.72–60.05% at 1 mg/mL. The ethyl acetate fraction showed 14.91% melanin inhibitory activity at a concentration of 10 µg/mL compared to the α-MSH treatment group. The protein expression inhibition rates of MITF, tyrosinase, TRP-1, and TRP-2 in the ethyl acetate fractions were 14.05%, 72%, 93.05%, and 53.44%, respectively, at a concentration of 10 µg/mL, compared to the control. These results indicate that SCW treatment could be used to develop cosmetic materials and functional food with physiological activity, and that SCW-treated rutin can be used as a skin-whitening cosmetic material.